The Inadequacies of Assigning “My Philosophy of Education” Statements in Teacher Education Courses - Bakker, Colin; Dubensky, Kate; Harvey, Lyndze; McDonough, Graham P. (Philosophical Inquiry in Education, 2019)
In teacher education programs, there is a prevalent belief that having teacher candidates compose personalized ‘my philosophy of education’ (MPE) statements is a valuable exercise that prepares them for the teaching profession. This paper argues that the prevailing intentions for, and common practice of, assigning these MPE statements to teacher candidates are problematic because they distort both the discipline of philosophy and the purpose of philosophy of education courses. The argument’s first section situates the practice of assigning MPE statements within the context of teacher education programs’ strong commitments to social constructivism and the reflective practitioner, and relates the problems associated with those commitments. It then reviews literature that describes the common properties and practices of assigning MPE statements. The second and third sections then develop the arguments that MPEs rely on and reinforce distortions of philosophy as a discipline and misconceptions about the purposes of philosophy of education courses in teacher education programs. Those two arguments share a theme that MPE statements reduce philosophy and philosophizing about education to declaring and clarifying an unexamined personal commitment, and hence drift toward enabling relativism. Finally, the conclusion relates how, in conjunction with those distortions, the use of MPE statements has acquired the function of certifying a teacher’s suitability to fit within the status quo. This situation, it claims, unfortunately distracts candidates and others in the teaching profession from developing their critical philosophical skills in responding to the epistemic, moral, and political realities of education and schooling.